Chronic disturbance induces attenuation of the acute glucocorticoid response in an urban adapter, the dark-eyed junco - Hanauer, Rachel E.; Abolins-Abols, Mikus; Brenner, Abigail M.; Gall, Baili J.; Ketterson, Ellen D. (Frontiers in Bird Science, 2023)
Urban birds' stress response frequently differs in magnitude from non-urban conspecifics. This urban phenotype may reflect response to selection, sorting during colonization of urban environments, developmental plasticity, or phenotypic flexibility in response to urban environments. We investigated whether exposure to one characteristic of an urban environment, chronic disturbance, could induce an attenuated acute glucocorticoid response over a short time in adult non-urban dark-eyed juncos (Junco hyemalis), which, if true, would support the phenotypic flexibility hypothesis. We tested this during the period of spring gonadal recrudescence. We simulated a high-disturbance urban-like environment by exposing non-urban experimental birds to chronic disturbance (30-min psychological stressors 4x/day for 3 weeks); controls were minimally disturbed. We found that chronically disturbed birds had a lower acute corticosterone response after 3 weeks of treatment. Baseline corticosterone was not affected.Chronically disturbed birds had less body fat and lower body condition than controls at the end of the experiment, although on average all birds gained weight over the course of the experiment.Feathers grown during the experiment did not show an effect of the disturbance treatment on feather corticosterone or fault bars, although captive-grown feathers had lower corticosterone and more fault bars than wild-grown feathers. We conclude that adult male juncos have the capacity to attenuate their acute corticosterone response in an environment with high frequency of disturbance, potentially facilitating colonization of urban habitats. Future research may show whether successful urban colonists differ from unsuccessful species in this regard.